INTENSIFIKASI PEMUNGUTAN DAN EKSTENSIFIKASI SUMBER PAD TERHADAP KEMANDIRIAN KEUANGAN DAERAH PEMEKARAN: STUDI PADA KABUPATEN SERAM BAGIAN BARAT DAN KABUPATEN KEPULAUAN ARU PROVINSI MALUKU - Meiske Wenno (Jurnal Cita Ekonomika, 2017)
This research discussing the finance self-support problem by using intensification of collection and extensification of PAD source at the government of West Seram District and Aru Island District, Maluku Province. The objective of research is to test and analyzing the factors establishing the intensification of collection and extensification of PAD source, to test and analyzing the effect of intensification of collection and extensification of PAD source on local finance self-support, and recommending a strategy to the government of West Seram District and Aru Island District in pursuance of the local finance self-support. Population this research is civil servants on the government office at West Seram District and Aru Island District who runs the function as assigned to manage and to produce PAD amounts 744 civil servants in the scope of the government office at West Seram District and Aru Island District. This research use factor analysis and multiple regression analysis. Result of research indicates that the implementation of intensification of collection and extensification of PAD source in the government at West Seram District and Aru Island District have significantly influenced the improvement of local finance self-support.